PRONUNCIATION ANXIETY AND PROFESSIONAL IDENTITY FORMATION EXPERIENCES OF INDONESIAN PRE SERVICE EFL TEACHERS - Erika Fitri; Movi Riana Rahmawanti; Wilda Rahayu Agustin (JETA (Journal of English Teaching and Applied Linguistic), 2026)
Pronunciation anxiety (PA) is one of the psychological factors that affects how pre-service EFL teachers develop their confidence and professional identity as future teachers.  Despite growing research on PA in language learning contexts, studies that specifically examine how PA is reflected in the professional identity formation of Indonesian pre-service EFL teachers remain limited. This study aimed to explore the types of pronunciation anxiety experienced by pre-service EFL teachers and to describe how PA affected their professional identity. This study used a mixed-method design, combining a four-point Likert-scale questionnaire administered to 30 participants and semi-structured interviews conducted with 15 participants from an English Education Study Program at one university in Bogor, Indonesia. The quantitative findings show that fear of negative evaluation (M=2.77) and pedagogical pronunciation anxiety (M=2.73) were the most dominant types of PA, both falling within the high category, while communication apprehension (M=2.50) also fell in the high category. Accent anxiety (M=2.47) and segmental/suprasegmental anxiety (M=2.40) fell within the low category. The qualitative findings show that pronunciation anxiety affects pre-service teachers' self-confidence, teaching readiness, and professional identity. Although good pronunciation is often associated with a prospective teacher’s professionalism, most view professional identity as something that is shaped through learning and experience. Therefore, pronunciation anxiety can influence the process of professional identity formation among prospective teachers of English as a foreign language.